GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 727 species occurrences available in GBIF matching the query: TaxonKey: Hyla picta (Günther, 1901) Country: Mexico. The dataset includes 727 records from 21 constituent datasets: 2 records from Museum of Comparative Zoology, Harvard University. 34 records from CM Herps Collection. 2 records from LACM Vertebrate Collection. 1 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto) Herpetofauna. 4 records from Sistematización de las colecciones científicas del Instituto de Historia Natural y Ecología, (IHNE) Chiapas. 8 records from Formación de la colección de referencia de anfibios y reptiles de la Reserva de la Biosfera de Sian Ka'an. 24 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 33 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 1 records from LSUMZ Herp Tissues. 3 records from University of Florida Herpetology. 142 records from Herps Specimens. 27 records from LSUMZ Herps Collection. 41 records from Coleccion de Herpetologia, MZFC-UNAM. 2 records from TNHC Herpetology Collection. 41 records from Colección Herpetológica del Museo de Zoología "Alfonso L. Herrera", México (MZFC, UNAM). 45 records from UTA Herpetology. 46 records from UMMZ Herpetology Collection. 11 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 6 records from UTEP Vertebrates. 109 records from KUBI Herpetology Collection. 145 records from Field Museum of Natural History (Zoology) Amphibian and Reptile Collection. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences